Associations between alcohol‐use and depression symptoms in adolescence: Examining gender differences and pathways over time. (4th February 2017) - Danzo, Sarah; Connell, Arin M.; Stormshak, Elizabeth A.
ABSTRACT: Several studies examining alcohol use and depression in youth have focused on documenting prevalence of overlap, or temporal ordering in longitudinal samples. Fewer studies have examined pathways connecting alcohol use and depression over time. This study examined gender differences between depression and alcohol use across adolescence while examining peer and family pathways as possible mediators of effects. Data was collected longitudinally from 593 families from three urban public middle schools in the United States. Participants were recruited in 6th grade and followed through 9th grade. We examined gender differences using a nested model comparison approach. Results indicated the association between depression and alcohol use differs by gender. For males, depression and alcohol use were independent across adolescence, and no significant indirect pathways were observed. For females, bidirectional effects were found between alcohol use and depression, as well as an indirect effect from depression to alcohol use via peer deviance.